(untitled) (Journal of Production Engineering, 1984)
The importance of workpiece temperatures on which the work-piece is treated, on the basis of the possible errors at the machining surface, the machining accuracy, and the possibility of their use for the indirect determination of the cutting tool wear in the machining flow was considered in the paper. On the basis of the developed methodology design of the experiments, the expressions for the temperature on the two characteristic positions on the workpiece area: wear the contact of the back surface of the tool and the workpiece (POSITION 1) and rotated for 90° tn rotating direction of the workpiece in addition to the previous position (POSITION 2), are determined.